Effects of long-term exposure to low-concentration PS-NPs on anammox granular sludge: Resistance and inhibition depend on PS-NP accumulation. (10th September 2022) - Xu, Shanshan; Li, Hanxiang; Wang, Gonglei; Liu, Zhiping; Long, Man; Guo, Jinsong; Yan, Peng; Chen, Youpeng; Fang, Fang
Abstract: At present, the effects on anammox granular sludge (AnGS) of long-term exposure to low-concentration polystyrene nanoplastics (PS-NPs) and the associated mechanisms are still unclear. In this paper, the effects of continuous PS-NP exposure (1–2 mg/L, 225 d) on the nitrogen removal performance, activity and granule stability of an AnGS reactor were studied. In the first 100 d, the nitrogen removal performance of the reactor was stable, and the specific anammox activity (SAA) gradually increased. After 225 d, the nitrogen removal performance of the reactor decreased, and the AnGS SAA NH4 + -N and SAA NO2 - -N decreased by 44.5% and 57.6%, respectively, compared with those at 100 d. Long-term PS-NP exposure increased the oxidative stress level of cells and led to membrane damage. Decreases in the content of extracellular polymeric substances (EPS) and extracellular protein (PN) hydrophobicity led to a decrease in the aggregation performance of AnGS. PS-NPs adhered to EPS to form a dense structure, blocking AnGS mass transfer channels and reducing AnGS strength, and some granular sludge was cracked. Candidatus Kuenenia and Candidatus Jettenia were inhibited, and their abundance decreased. The effects of PS-NP exposure on AnGS depended on the accumulation of PS-NPs, and significant inhibitory effects were observed at 118 mg PS-NPs/g VSS. This work helps to assess the potential risk of long-term AnGS exposure to low-concentration PS-NPs and is of great significance to maintain the high nitrogen removal performance and stability of AnGS. Graphical abstract: Image 1 Highlights: The effects of AnGS exposure to 1–2 mg/L PS-NPs for 225 d were studied. Increased accumulation of PS-NPs led to the inhibition of AnGS. PS-NPs reduced the SAA and stability of AnGS by plugging pores. Decreases in EPS content and PN hydrophobicity were the main contributors to AnGS disruption. AnGS disruption relieved the mass transfer resistance caused by PS-NPs.